2005
DOI: 10.1176/appi.ajp.162.2.394
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ketamine on Anterior Cingulate Glutamate Metabolism in Healthy Humans: A 4-T Proton MRS Study

Abstract: In humans as in animals, an acute hypofunctional NMDAR state is associated with increased glutamatergic activity in the anterior cingulate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
169
1
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 277 publications
(197 citation statements)
references
References 16 publications
24
169
1
3
Order By: Relevance
“…This is in accordance with the findings in human schizophrenia patients (Stanley et al, 1996;Theberge et al, 2003;Ohrmann et al, 2005) and healthy subjects exposed to ketamine (Rowland et al, 2005). Thus, the repeated administration might generate a better schizophrenia model than acute exposure and emphasizes the importance of the frontal and retrosplenial/cingulate cortex for the pathophysiology of schizophrenia.…”
Section: Effects Of Repeated Mk801 On Metabolism D Kondziella Et Alsupporting
confidence: 90%
“…This is in accordance with the findings in human schizophrenia patients (Stanley et al, 1996;Theberge et al, 2003;Ohrmann et al, 2005) and healthy subjects exposed to ketamine (Rowland et al, 2005). Thus, the repeated administration might generate a better schizophrenia model than acute exposure and emphasizes the importance of the frontal and retrosplenial/cingulate cortex for the pathophysiology of schizophrenia.…”
Section: Effects Of Repeated Mk801 On Metabolism D Kondziella Et Alsupporting
confidence: 90%
“…Although ketamine induces NMDA receptor hypofunction, acute ketamine leads to increased glutamate in the extracellular space in animals (Moghaddam et al, 1997) and increased glutamate in humans as measured by magnetic resonance spectroscopy (Rowland et al, 2005). Glutamate level is reduced in chronic schizophrenia (Theberge et al, 2003;Ohrmann et al, 2005Ohrmann et al, , 2007 but increased in early psychosis (Theberge et al, 2002;Bartha et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The one study that induced NMDA blockade in humans found increased Gln in the anterior cingulate. 76 Rowland et al used 1 H MRS to measure Gln levels, thus, indirectly assessing Glu neurotransmitter release. In contrast, our results indicated less Glu across the regions of interest in both twins with schizophrenia and their unaffected co-twins compared with controls.…”
Section: Discussionmentioning
confidence: 99%